Ovarian torsion in a primipara female dog in Brazil - dos Santos, Ivan Felismino Charas [UNESP]; Soares, Joice Franciele; de Azevedo, Maria Gabriela Picelli [UNESP]; Masseno, Ana Paula; Gomes, Mayara Viana Freire [UNESP]; da Silva, Bruna Martins [UNESP]; de Castro Martins, David José [UNESP]; Agostinho, Manuela [UNESP]; Rahal, Sheila Canevese [UNESP] (Universidade Federal do Rio Grande do Sul, 2018)
Background: Ovarian torsion is a condition which the ovary and the ovarian pedicle twist around the ovary suspensory ligament. No report regarding this condition was reported. The aim of the report was to describe a case of unilateral ovarian torsion in a 2-year-old primipara Golden Retriever dog. Case: A 2-year-old female primipara Golden Retriever dog weighting was referred to the Veterinary Hospital, for purulent vaginal discharge evaluation. The dog was presenting anorexia, weight loss, and intermittent diarrhea and vomiting. A cesarean section was performed nine months before her presentation and the oestrus cycle was recorded six months after the cesarean section. Discomfort was observed during the palpation of the abdomen and purulent vaginal was observed. Vaginal swab was performed and followed by cytological examination. The ultrasonographic examination was consistent with pyometra. The ovariohysterectomy was performed and were observed torsion of the left ovary. The histopathological examination of the left ovary and uterus were consistent with ovary necrosis and pyometra. Ten days after surgery the vaginal discharge had resolved and the sutures were removed. Six months postoperatively the dog revealed no further abnormalities. Grossly, the left ovary had firm consistency, dark red surface and 8 cm diameter. The histopathology examination findings were consistent with a diagnosis of diffuse necrosis of left ovary due to ovarian torsion, and uterine suppurative inflammatory process - pyometra. Discussion: Ovarian torsion is uncommon in small animals, but can be observed high incidence in pregnant female dogs than in non-pregnant ones. The 360ºan asynchronous ovarian torsion described in the present case is also an unusual condition in primipara female dogs due to the smaller stretching of the ovary suspensory ligament. The ovarian torsion is considerate an emergency condition due to acute abdominal pain. The mild abdominal discomfort observed during the physical examination was associated to pyometra or to ovarian torsion. The histopathological findings as hemorrhage, edema and necrosis were associated to compromised arterial circulation and ovarian torsion in late stage. The size of the pregnant uterus and/or the pyometra has contributed to ovary torsion. The dog of the present report had pyometra and previous cesarean sections; and these conditions may have contributed to ovarian torsion. The condition was incidentally found during the ovariohysterectomy, and the ovarian torsion diagnosis was determinate through histopathological examination. Computed tomography and magnetic resonance image could be used to diagnose, furthermore, they were not conducted due to the high cost. The leukocytosis and red blood cells Rouleaux was associated with ovarian necrosis and pyometra. Ovariohysterectomy was the treatment of choice to pyometra and ovarian torsion, and the surgery was performed without ovarian torsion reversion to minimize the reperfusion lesions. Ovarian torsion is a rare event in dogs, and it was clinically diagnosed during the surgery. To the best of the authors' knowledge, this is the first report of ovarian torsion associate with pyometra in primipara female dogs in Brazil.
Keywords: Dog; Endometrium; Obstetric; Ovary; Pyometra complex